Wiley, John interview - Emon, Ayeshah; Emon, Ayeshah (My University, 2010)
Dr. John D. Wiley was the Chancellor for the University of Wisconsin-Madison between 2001-2008. He currently serves as the interim director of the Wisconsin Institutes for Discovery. This interview documents his involvement in the early development and conceptualization of the Wisconsin Institutes for Discovery.